2021
DOI: 10.1101/2021.04.16.440220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting the Genomic Resolution of Bulk Segregant Analysis

Abstract: Bulk segregant analysis (BSA) is a technique for identifying the genetic loci that underlie phenotypic trait differences. The basic approach of this method is to compare two pools of individuals from the opposing tails of the phenotypic distribution, sampled from an interbred population. Each pool is sequenced and scanned for alleles that show divergent frequencies between the pools, indicating potential association with the observed trait differences. BSA has already been successfully applied to the mapping o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(46 reference statements)
1
0
0
Order By: Relevance
“…We simulated a series of pool numbers to evaluate the absolute bias and signal-to-noise ratio across different numbers of pools; our results indicated that greater numbers of bulked pools improve the mapping resolution of BSA (Supplemental Figure 5). As previously reported, more bulked individuals increases recombination events in BSA (Shen and Messer, 2022). Our statistical results confirmed that better dissection could be obtained using multiple pools (Supplemental Figures 2-5).…”
Section: Molecular Plantsupporting
confidence: 90%
“…We simulated a series of pool numbers to evaluate the absolute bias and signal-to-noise ratio across different numbers of pools; our results indicated that greater numbers of bulked pools improve the mapping resolution of BSA (Supplemental Figure 5). As previously reported, more bulked individuals increases recombination events in BSA (Shen and Messer, 2022). Our statistical results confirmed that better dissection could be obtained using multiple pools (Supplemental Figures 2-5).…”
Section: Molecular Plantsupporting
confidence: 90%